Determinación del índice topográfico de humedad para el diagnóstico del riesgo por desbordamiento fluvial en el cantón Flavio Alfaro - Cueva Schettini, Erick Yair (2024)
This study analyzes the risk of river overflow in the Flavio Alfaro canton, Manabí, Ecuador, using the Topographic Wetness Index (TWI), which is fundamental in hydrological analysis. Digital Elevation Models (DEMs) were used to examine surface runoff patterns and terrain slope to identify areas vulnerable to flooding. The methodology included Multi-Criteria Analysis (MCA) and remote sensing through Geographic Information Systems (GIS), applying specialized algorithms to calculate the TWI and its relationship with river risk. An unsupervised classification of the TWI allowed the segmentation of the territory into risk levels (low, moderate, high, and very high) based on runoff concentration. The results indicate that approximately 76.9 km² of the territory fall within high and very high-risk levels, areas prone to water accumulation during periods of heavy rainfall. The TWI proved to be a key factor, as areas with high values of this index coincided with critical water accumulation points, increasing the flood risk. With a total of 96.0 km² in highly vulnerable areas, the diagnosis emphasizes the need for a Territorial Development Plan that incorporates mitigation measures and sustainable water resource management to reduce exposure to adverse hydrological events.